Legal Protection of Creditors in Credit Agreements at Swastisari Kupang Credit Union - Rade, Stefanus Don; Tae, Mericiana Yulita Fin; Asman, Firgilius Kandro Mego; Huler, Kalistus G. Wayong (PT. Riset Press International, 2023)
Credit Unions have an important role in improving the economy of the Indonesian people through joint efforts based on family principles, so cooperatives need to develop themselves further and be built to be strong and independent based on cooperative principles. In running its business, the suitable implements credit, a form of effort to process the capital owned from deposits and member donations, to achieve optimal results. A credit agreement is needed to avoid bad credit in the future as evidence of a contract between the creditor and the debtor. This is a reference to legal protection for the debtor. This research was conducted through the empirical juridical method using primary data sources, namely data obtained directly in the field. In terms of providing credit and collateral, there is often negligence by the debtor to the creditor. Hence, the creditor, in this case, the Swastisari Kupang Credit Cooperative, has a very interesting strategy as a reference for recovery, namely by checking loan files, surveys, credit analysis by applying the 5C principle, billing control by checking data periodically to find out the condition or condition of the borrowing member. In addition, the cooperative makes rescheduling, restructuring, and reconditioning to achieve mutual welfare based on the principle of kinship.